Effect of Service Quality on Satisfaction Among Toddler Mothers in Ben Mari Kendalpayak Hospital - Syagran, Evy Afiyah (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Service quality is an indicator of hospital visitor satisfaction. A sick toddler's new visit for the past three years in the Mari Kendalpayak Hospital shows a positive trend. This study aims to determine the effect of service quality including responsiveness, reliability, assurance, empathy and tangible of visitor satisfaction. Method: The survey of 62 respondents from 148 mothers of children under five who visited Ben Mari Kendalpayak Hospital since December in 2017 until March in 2018 Independent variables were service quality including responsiveness, reliability, assurance, empathy and tangible. While the dependent variable is satisfaction. This study uses an instrument in the form of a questionnaire. This study uses multiple linear regression methods for data analysis. Results: Most respondents rated the quality of hospital services as good as capturing, reliability, assurance, empathy and tangible. Meanwhile, hospital service satisfaction was also considered good by most respondents. The five determinants of hospital service quality have been shown to influence visitor satisfaction. But the responsiveness variable has a dominant influence on visitor satisfaction. Conclusion: This study was successful in finding that responsiveness, reliability, assurance, empathy and tangible influence visitor satisfaction. Ben Mari Kendalpayak Hospital Management needs to pay more attention to the problem of catching visitors because good responsiveness can give comfort for visitors.